Pengaruh Pemberian Jus Tomat Terhadap (Lycopersicum Commune) Terhadap Perubahan Tekanan Darah Pada Wanita Menopause Kel. Campurejo Kec.Mojoroto Kota Kediri - Pradian, Galuh; Nasution, Ade Saputra; Sholehah, Khusnul Makhatul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2018)
Tomato is one of diets that is rich of nutrition. Moreover, tomato has an important role to keep body balance, tomato also can be used to cure hypertension. Tomato contains potassium, calcium, and other nutrition that can decrease blood pressure of menopause women. This study is aimed at knowing the influence of tomato juice towards blood pressure change of menopause women. The sample used in this study is 16 respondents. The design of the study is pre experimental with one group pre-test and post-test approach. The data analysis used in this study is Wilcoxon test. The result of the study shows that there is an influence of tomato juice towards the decreasing of systolic blood pressure of menopause women in campurejo-mojoroto-kediri. It is hoped that the result of this study will give a beneficial contribution to menopause women and other hypertension sufferers.Keyword: Hypertension, Tomato, Potassium, Calcium